Installing An Anti-Bullying Attitude Through Civics Learning at MIS Nur Athifa - Aminah, Siti; Aulia, Tazkya (Yayasan Pendidikan Islam Akmalia, 2023)
Education has an important role in shaping one’s personality. In essence, education has two goals, namely helping people to be smart and encouraging people to be better. But lately moral damage is rife, deviant behavior, ethics, morals, and law, from mild to severe, are often shown by students and students from high school and even elementary schools. With this in mind, the role of the Pancasila and Citizenship Education teacher really needs to be in addition to educating and teaching, it is also appropriate to try to prevent issues of bullying behavior. In addition, PPKn teachers have a strong relationship with inculcating character values ​​so that students become individuals who have better personalities. Therefore, with this research instilling an anti-bullying attitude through Pkn learning, it forms good character in students. Citizenship Education also has a mission, namely to increase the potential of children, prepare children to live in society, and form a culture of citizenship as one of the determinants of a democratic life.